Synthesis of phenolic compounds from virgin olive oil and their biological evaluation - Martins, B.T. (2024)
"In recent years, investigating the bioactive compounds from natural sources, and their synthesis, has garnered significant attention due to their biological benefits. Among these, the phenolic compounds in extra virgin olive oil (EVOO) have been recognised for their diverse biological activities, including antioxidant, anti inflammatory and antiproliferative effects. This thesis delves into the synthesis, stability and biological evaluation of hydroxytyrosol (HT) and its derivatives, as well as the development of innovative synthetic strategies for the obtention of oleocanthal and oleacein, two other important phenolic compounds in EVOO. One of the main goals of this research was to develop efficient and scalable synthetic methods for HT and its derivatives, as detailed in Chapter 2. This chapter presents novel approaches for the regioselective synthesis of HT glucuronides and sulfates, overcoming challenges related to regioisomeric mixtures and paving the way for further biological studies."